Development of Acid-Base Devices Integrating ARCS Motivation Strategy in Problem-Solving Learning Model Scientific Attitude and Critical Thinking Skills of Students - Melania Priska; Natalia Peni; Yosephina Payu Wao (Postgraduate, University of Mataram, 2021)
The purpose of this research is to develop an acid-base device that integrates ARCS motivation strategies in problem-solving learning models of scientific attitudes and critical thinking skills of students. The development of this device uses a 4-D model, but in this study, due to the limited time, the development of the device only reached the development stage and was tested on Biology Education Study Program students in semester 2 with a one-group pretest-posttest design. Data collection techniques used are validation, tests, and questionnaires. Data were analyzed using SPSS and the Likert scale. The results showed the validity of the Semester Lesson Plan obtained a rcount of 0.690, valid category. Student Worksheet obtained rcount value of 0.748 valid categories. Learning Outcomes Test obtained, rcount of 0.701, with a valid category. The percentage of Lesson Plan implementation is on a scale of 4 with a good category. The results of the N-Gain Score test in the productive class is 78.58% effective category while the N-Gain Score in the trial class is 70.14% and is included in the quite effective category. The data shows that learning using ARCS motivation strategies in problem-solving learning models can improve student learning outcomes.